Low expression of the CCL5 gene and low serum concentrations of CCL5 in severe invasive group a streptococcal disease - Kailankangas, V.; Katayama, S.; Gröndahl-Yli-Hannuksela, K.; Vilhonen, J.; Tervaniemi, MH; Rantakokko-Jalava, K.; Seiskari, T.; Lönnqvist, E.; Kere, J.; Oksi, J.; Syrjänen, J.; Vuopio, J. (Springer Nature, 2025)
Purpose: Our objective was to elucidate host dependent factors of disease severity in invasive group A Streptococcal disease (iGAS) using transcriptome profiling of iGAS cases of varying degrees of severity at different timepoints. To our knowledge there are no previous transcriptome studies in iGAS patients.
Methods: We recruited iGAS cases from June 2018 to July 2020. Whole blood samples for transcriptome analysis and serum for biomarker analysis were collected at three timepoints representing the acute (A), the convalescent (B) and the post-infection phase (C). Gene expression was compared against clinical traits and disease course. Serum chemokine ligand 5 (CCL5, an inflammatory cytokine) concentration was also measured.
Results: Forty-five patients were enrolled. After disqualifying degraded or impure RNAs we had 34, 31 and 21 subjects at timepoints A, B, and C, respectively. Low expression of the CCL5 gene correlated strongly with severity (death or need for intensive care) at timepoint A (AUC = 0.92), supported by low concentrations of CCL5 in sera.
Conclusions: Low gene expression levels and low serum concentration of CCL5 in the early stages of an iGAS infection were associated with a more severe disease course. CCL5 might have potential as a predictor of disease severity. Low expression of genes of cytotoxic immunity, especially CCL5, and corresponding low serum concentrations of CCL5 associated with a severe disease course, i.e. death, or need for intensive care, in early phase of invasive group A Streptococcal disease.